Dimerized Domain V of Beta2-Glycoprotein I Is Sufficient to Upregulate Procoagulant Activity in PMA-Treated U937 Monocytes and Require Intact Residues in Two Phospholipid-Binding Loops - Kolyada, Alexey (Antibodies (Basel), 2017)
Upregulation of the procoagulant activity of monocytes by antibodies to beta2-glycoprotein I (β2GPI) is one of the mechanisms contributing to thrombosis in antiphospholipid syndrome. Current knowledge about receptors responsible for the upregulation of procoagulant activity by β2GPI/anti-β2GPI complexes and their binding sites on β2GPI is far from complete. We quantified the procoagulant activity expressed by phorbol 12-myristate 13-acetate (PMA)-differentiated U937 cells by measuring clotting kinetics in human plasma exposed to stimulated cells. Cells stimulated with anti-β2GPI were compared to cells treated with dimerized domain V of β2GPI (β2GPI-DV) or point mutants of β2GPI-DV. We demonstrated that dimerized β2GPI-DV is sufficient to induce procoagulant activity in monocytes. Using site-directed mutagenesis, we determined that the phospholipid-binding interface on β2GPI is larger than previously thought and includes Lys308 in β2GPI-DV. Intact residues in two phospholipid-binding loops of β2GPI-DV were important for the potentiation of procoagulant activity. We did not detect a correlation between the ability of β2GPI-DV variants to bind ApoER2 and potentiation of the procoagulant activity of cells. The region on β2GPI inducing procoagulant activity in monocytes can now be narrowed down to β2GPI-DV. The ability of β2GPI-DV dimers to come close to cell membrane and attach to it is important for the stimulation of procoagulant activity.